(untitled) - Kusumaningrum, Harsi Dewantari (Wageningen, 2003)
Illness resulting from consumption of contaminated food is a continuous serious public health problem in the world. A proportion of this foodborne disease is attributable to improper preparation practices in the home, including cross-contamination.
Keywords: Salmonella,Pathogenic bacteria,Vi khuẩn gây bệnh